PENGARUH ADOPSI PAJAK ELEKTRONIK E-SAMSAT DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KOTA CIMAHI - Yusuf Krisna Hari; Kurhayadi Kurhayadi; Susniwati Susniwati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to analyze the effect of work motivation and leadership on employee performance with work discipline as an intervening variable. This research is quantitative research. Quantitative research methods were used to examine the samples by using saturation sampling method sourced from the data of LPP TVRI NTT Station office employees totaling 54 people. Data collection techniques using a questionnaire, while data analysis uses SmartPLS. The results of the study show that: (1) leadership has a positive and significant impact on work discipline, (2) work motivation can have a positive and significant impact on work discipline, (3) work discipline can have a positive influence and have a significant impact for employee performance, (4) leadership can have a positive impact and significant change on employee performance, (5) work motivation can have a positive impact and significant influence on employee performance, (6) leadership has a positive impact and significant influence on employee performance in the context of work discipline, and (7) work motivation can have a positive impact and significant implications for employee performance in terms of work discipline.